A new and improved explanatory account of international law - Chehtman, Alejandro Eduardo (2021)
Miodrag Jovanović has written an important account of why international law must be considered law. In this short review, I argue that his account succeeds at the cost of weakening a central feature of law, namely, its distinct normative force. By contrast, I suggest that we have the conceptual and descriptive tools needed to defend a more robust understanding of international law as providing its subjects with weighty reasons for action.